(3eaGgje efgLjI hMGdGJ YedjIs - (3CMeO jhSa(B, (3OhOjfs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY hGdWHGYI(B,s, 2021)
(3jgOa gPG GdcJGH Edi HfGA hJfejI GdeaGgje GdMOjKI aj GdEOGQI GdGSJQGJjLjI, eY JSdjW GdVhA Ydi GdacQ GdGSJQGJjLj hGdeeGQSGJ GdGSJQGJjLjI GdeJHYI aj gPG GdeLGd(B. (3GdgOa GdCSGSj gh Jecjf efXeGJ GdCYeGd ef GdJcja HfLGM eY GdHjFI GdNGQLjI GdeJZjQI, hGdGSJaGOI ef GdaQU GdeJGMI, hehGLgI GdJMOjGJ GdJj bO JYhb fehgG(B. (3HGdEVGaI Edi Pdc, jSGge GdcJGH aj JMdjd GdYfGUQ GdGSJQGJjLjI OGNd GdefXeI faSgG, eeG jSGYO aj JYRjR fbGW GdbhI heYGdLI fbGW GdVYa(B.(3eMJhi GdcJGH(B: (3jZWj GdcJGH eLehYI hGSYI ef GdehVhYGJ GdeJYdbI HGdEOGQI GdGSJQGJjLjI HWQjbI TGedI hhGVMI, eY JbOje CeKdI YedjI dJSgjd age GdeaGgje GdeYbOI(B. (3jJchf GdcJGH ef YTQI aUhd JZWj GdLhGfH GdCSGSjI ddEOGQI GdGSJQGJjLjI, HOkAG ef GdeaGgje GdCSGSjI hUhkdG Edi GdJNWjW hGdJfajP hGdQbGHI GdGSJQGJjLjI(B.(3GdaUhd(B: (3GdaUd GdChd(B: (3jbOe fXQI YGeI Ydi GdeaGgje GdCSGSjI ddEOGQI GdGSJQGJjLjI(B.(3GdaUd GdKGfj(B: (3jJfGhd GdJhLgGJ GdGSJQGJjLjI GdJj JJHYgG efXeGJ GdCYeGd(B.(3GdaUd GdKGdK(B: (3jQcR Ydi GdJMdjd GdGSJQGJjLj ddHjFI GdOGNdjI hGdNGQLjI ddefXeI(B.(3GdaUd GdQGHY(B: (3jTQM YedjI GdJNWjW GdGSJQGJjLj(B.(3GdaUd GdNGeS(B: (3jZWj UjGZI GdGSJQGJjLjI hGdNWI GdGSJQGJjLjI(B.(3GdaUd GdSGOS(B: (3jSJYQV GdHOGFd hGdNjGQGJ GdGSJQGJjLjI GdeJGMI(B.(3GdaUd GdSGHY(B: (3jJfGhd YedjI JfajP GdGSJQGJjLjI(B.(3GdaUd GdKGef(B: (3jQcR Ydi GdQbGHI GdGSJQGJjLjI hbjGS hJbjje GdCOGA(B.(3GdaUd GdJGSY(B: (3jTQM eaghe HWGbI GdCOGA GdeJhGRfI cCOGI ddbjGS hGdJNWjW GdGSJQGJjLj(B.(3GdaUd GdYGTQ(B: (3jbOe eLehYI ef GdMGdGJ GdOQGSjI GdYedjI GdJj JhVM JWHjb GdeaGgje GdfXQjI aj GdhGbY(B.(3GdahGFO(B:(3jhaQ GdcJGH agkeG TGedkG deHGOF GdEOGQI GdGSJQGJjLjI(B.(3jSGYO aj JWhjQ GdegGQGJ GddGReI dGJNGP GdbQGQGJ GdGSJQGJjLjI GdUGFHI(B.(3jbOe COhGJ hCSGdjH YedjI dJMdjd GdHjFI hJWhjQ GdGSJQGJjLjGJ(B.(3jYJHQ eQLkYG bjkeG ddWdGH hGdHGMKjf heOjQj GdCYeGd Ydi MO ShGA(B.(3HGNJUGQ, gPG GdcJGH gh Odjd TGed ddEOGQI GdGSJQGJjLjI, jgOa Edi JRhjO GdbGQF HGdCOhGJ hGdeYQaI GddGReI dHfGA hJfajP GSJQGJjLjGJ fGLMI JSGge aj JMbjb CgOGa GdefXeI(B.s
(3GdeQGLY U(B.42.67.103.134.157.187.211.237.273.307 s
Keywords: (3GdEOGQI GdGSJQGJjLjIs; (3GdJNWjW GdGSJQGJjLjs